Analyzing Spatio-temporal Pattern of Crop Diversification in Jalandhar District of Punjab, India - Sajjad , Haroon; Prasad, Sandip (Asian Journal of Agriculture and Rural Development, 2014)
This paper analyzed dynamics of crop diversification in one of the agriculturally prosperous districts of Indian Punjab using Gibbs Martin Index. Spatio-temporal analysis of crop diversification in the district shows decline in crop diversification in most of the blocks (administrative sub divisions). The cropping pattern in most of the blocks of the district has become over specialized in the favour of rice-wheat rotation. Net irrigated area is continuously increasing for the cultivation of rice and wheat in the study area. Declining diversity of crops in the district has serious repercussions for natural resources, ecology and socio-economic condition of the farmers.